Gold-bearing ferroselite (FeSe2) from Trogtal, Harz, Germany, and significance of its Co/Ni ratio - Cabral,A.R.; Koglin,N.; Bratz,H. (Journal of Geosciences, 2012)
Ferroselite from Trogtal, the type locality of the cobalt selenide trogtalite, in the Harz Mountains, Germany, forms a trogtalite-ferroselite assemblage in pockets of massive clausthalite in which specular hematite is dispersed. The pockets occur in hematite-impregnated carbonate veins, emplaced in a reddened greywacke of Lower Carboniferous age. Ferroselite contains ˜0.2-5.0 ppm Au; trogtalite has even higher Au contents. Ferroselite has Co/Ni ratios mostly above unity. These characteristics likely reflect oxidizing brines with Co/Ni > 1, such as those involved in the formation of sediment-hosted copper deposits.
Keywords: ferroselite; trogtalite; Co/Ni ratio; Trogtal; Harz; Germany